2020
DOI: 10.1186/s13098-020-00565-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk and predictors of in-hospital mortality from COVID-19 in patients with diabetes and cardiovascular disease

Abstract: Background: Diabetes mellitus (DM) and cardiovascular disease (CVD) are present in a large number of patients with novel Coronavirus disease 2019 (COVID-19). We aimed to determine the risk and predictors of in-hospital mortality from COVID-19 in patients with DM and CVD. Methods: This retrospective cohort study included hospitalized patients aged ≥ 18 years with confirmed COVID-19 in Alborz province, Iran, from 20 February 2020 to 25 March 2020. Data on demographic, clinical and outcome (in-hospital mortality)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 37 publications
5
43
2
3
Order By: Relevance
“…The majority of prior research has focused on the association between having diabetes history instead of blood sugar levels and COVID-19 fatality risk. Therefore, almost similar to our findings, some research and review articles found a negative association between hyperglycemia, weak glycemic control, and diabetes with COVID-19 fatality [3,7,12,[20][21][22][23][24][25]. As such, a recent systematic review recommended that health care providers consider monitoring blood glucose levels to be lower than 180 mg/dl (without triggering hypoglycemia) in most diabetic patients who have COVID-19 [7].…”
Section: Glycaemia and Covid-19 Mortalitysupporting
confidence: 89%
See 3 more Smart Citations
“…The majority of prior research has focused on the association between having diabetes history instead of blood sugar levels and COVID-19 fatality risk. Therefore, almost similar to our findings, some research and review articles found a negative association between hyperglycemia, weak glycemic control, and diabetes with COVID-19 fatality [3,7,12,[20][21][22][23][24][25]. As such, a recent systematic review recommended that health care providers consider monitoring blood glucose levels to be lower than 180 mg/dl (without triggering hypoglycemia) in most diabetic patients who have COVID-19 [7].…”
Section: Glycaemia and Covid-19 Mortalitysupporting
confidence: 89%
“…On the other hand, COVID-19 intensifies the complications and prognosis of diabetes, such as diabetic ketoacidosis. However, it is not well-understood whether blood sugar directly affects SARS-CoV-2 infection progression or the virus changes carbohydrates' metabolism [9,12,13,20,26].…”
Section: Glycaemia and Covid-19 Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely reported that most deaths occurred among patients with at least one underlying disease, such as hypertension [4] and diabetes mellitus [5]. A meta-analysis of seven clinical studies performed in China identified chronic obstructive pulmonary disease (COPD), cardiovascular disease, and hypertension as risk factors for severe disease and intensity care unit (ICU) admission [6].…”
mentioning
confidence: 99%